Швидке перетворення Фур’є модульованих сигналів, представлених рядом Фур'є двох змінних - Вербицький, Євген Володимирович (НТУ "ХПІ", 2018)
У статті описано принцип представлення модульованих сигналів на основі ряду Фур’є двох змінних. Показано переваги незалежного опису несучої і модулюючої функцій. Наведено формули розрахунку спектральних складових і гармонік на основі ряду Фур’є двох змінних. Отримано дискретизовані формули для розрахунку спектру на основі ряду Фур’є однієї та двох змінних. Показано доцільність використання формул швидкого перетворення Фур’є для зменшення обсягу математичних розрахунків. Проведено адаптацію методики швидкого перетворення Фур’є для розрахунку спектру модульованих сигналів на основі ряду Фур’є двох змінних, для чого додатково здійснюється процедура сумування та перегрупування гармонік за номером. Проведено аналіз трудомісткості розрахунків за пропонованою методикою розрахунку спектру та показано в скількі разів вона зменшується у порівнянні з безпосереднім розрахунком спектру за початковими формулами.

Pulse modulated signals is useful to represent based on double Fourier series. The article describes the principle of representation of modulated signals based on double Fourier series. The advantages of an independent description of carrier and modulating functions are shown. The expediency of using the double Fourier series to analyze the spectrum of modulated signals, where the modulation multiplicity does not have an integer value, or the law of modulation or carrier functions change is parametric, which may cause the appearance of subharmonic oscillations, is shown. The formulas for calculating the spectral components and harmonics on the basis of the Fourier series of two variables are given. The discrete formulas for calculating the spectrum based on Fourier series of one and two variables are obtained. It is shown the expediency of using Fourier transforms to reduce the amount of mathematical calculations. The adaptation of the Fast Fourier Transform method to the calculation of the spectrum of modulated signals based on the double Fourier series is carried out, in addition, the procedure of summation and rearrangement of harmonics by the number is carried out. The number of the function descrete values for given number of spectrum harmonics based on Kotelnikov theorem are estimated. An analysis of the complexity of calculations according to the proposed method for calculating the spectrum and shows how many times it decreases in comparison with the direct calculation of the spectrum by the initial formulas. The recommendations for spectrum calculation proposed based on proposed procedure depend on descrete values of primary function are given.
A fast fourier transform of modulated signals based on double fourier series
Keywords: модульований сигнал; гармоніка; суммування; спектр сигналу; modulated signal